2018
DOI: 10.1016/j.jaad.2018.05.1254
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Drug survival of apremilast for psoriasis in a real-world setting”

Abstract: A total of 48 patients were included in the study. At the end of the study period, 35.41% (17/48) of our patients remained on apremilast, with treatment durations ranging 130-627 days compared with 50.6% in the Lee et al study. The patients who stopped taking apremilast (64.58%, 31/48) had treatment failures after an average of 169 days and a median of 144 days. No patient was lost to follow-up. Mean drug survival duration was 313 (95% confidence interval 247-378) days (Fig 1); and median drug survival was 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
1
12
2
Order By: Relevance
“…administration route and favorable safety profile. The drug survival rate of apremilast in our study was similar to those reported previously by Papadavid et al 4 and Ohata et al, 5 and higher than those reported by Lee et al 6 and Santos-Juanes et al 7 The median drug survival period was 453 days, which was longer than those in previous studies (12.5 weeks by Vujic et al 8 and 341 days by Lee et al). 6 Although apremilast is a relatively expensive drug in Japan, there were only two patients who discontinued apremilast due to economic reasons.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…administration route and favorable safety profile. The drug survival rate of apremilast in our study was similar to those reported previously by Papadavid et al 4 and Ohata et al, 5 and higher than those reported by Lee et al 6 and Santos-Juanes et al 7 The median drug survival period was 453 days, which was longer than those in previous studies (12.5 weeks by Vujic et al 8 and 341 days by Lee et al). 6 Although apremilast is a relatively expensive drug in Japan, there were only two patients who discontinued apremilast due to economic reasons.…”
Section: Discussionsupporting
confidence: 89%
“…and Ohata et al ., and higher than those reported by Lee et al . and Santos‐Juanes et al . The median drug survival period was 453 days, which was longer than those in previous studies (12.5 weeks by Vujic et al .…”
Section: Discussioncontrasting
confidence: 49%
“…A small number of retrospective studies have assessed the efficacy and safety of apremilast in routine practice . However, these results cannot be extrapolated to the entire population of patients with psoriasis, primarily because the sample sizes were small (from 34 to 131 patients).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Safety was not compromised on combining apremilast with other biologic agents in the management of psoriasis and PsA. [ 12 ] A retrospective study by Mayba and Gooderham has reported a better drug survival of apremilast in their patients who were also on other systemic agents (16%),[ 13 ] compared to poor drug survival reported in apremilast monotherapy (49%[ 14 ], 65%[ 15 ]). Hence, combining other systemic agents with apremilast may increase the treatment adherence of patients; however, additional therapeutic benefits in terms of efficacy or tolerability is subject of further research.…”
Section: Psoriasismentioning
confidence: 99%
“…[ 14 ] In another study, a failure rate of 65% was noted after a median duration of 200 days. [ 15 ] Hence, it appears that around half of the patients discontinue apremilast treatment within 6–8 months due to various reasons including lack of efficacy.…”
Section: Safety Tolerability and Drug Survivalmentioning
confidence: 99%